The Autocrat's Moral-Legal Dilemma: Popular Morality and Legal Institutions in China. (May 2021) - Ding, Iza; Javed, Jeffrey
Authoritarian regimes sometimes professionalize their legal systems to govern more effectively. Yet when quasi-autonomous courts rule in contradiction to popular conceptions of right and wrong—popular morality—it might threaten citizens' trust in the regime. We use the case of contemporary China to investigate this "moral-legal dilemma"—the competing needs of legal development and the satisfaction of popular justice concerns. Four case studies demonstrate that when court rulings conflict with popular morality, the party-state selectively alters decisions, so long as intervention does not significantly jeopardize the integrity of the legal system. Two online survey experiments then assess citizens' reactions to moral-legal conflict in court rulings. We find that people are more likely to experience "moral dissonance" when legal decisions conflict with popular morality. We do not find that moral-legal conflict in court rulings significantly undermines individuals' trust in the regime. Our analysis underscores the need for more attention to the moral foundations of authoritarian rule.